Factors contributing to declination of annual influenza vaccination by healthcare workers caring for cancer patients: An Australian experience. Issue 14 (27th March 2018) - Surtees, T.C.; Teh, B.W.; Slavin, M.A.; Worth, L.J.
Highlights: A declination form program was evaluated to identify factors associated with influenza vaccination. Minimal patient contact was significantly associated with lower vaccine uptake in staff HCWs. Self reported reasons for non-vaccination included potentially modifiable and non-modifiable factors. An 'upper threshold' of vaccination using a non-mandatory approach has likely been met. Abstract: Healthcare workers (HCWs) at an Australian cancer centre were evaluated using a voluntary declination form program to determine factors contributing to declination of annual influenza vaccination. Overall, 1835/2041 HCWs (89.9%) completed a consent or declination form; 1783 were vaccinated and 52 declined. Staff roles with minimal patient contact were significantly associated with lower vaccine uptake (adjusted odds ratio 0.48, 95% confidence interval 0.23–0.99). Reasons for vaccine refusal included personal choice (41%), previous side-effect/s (23.1%), and medical reasons (23.1%). Of these, a large proportion may not be amenable to intervention, and this must be considered in setting threshold targets for future campaigns.